OPTIMIZATION OF WINDOW WIDTH AND WINDOW LEVEL ON BONE WINDOW FOR EXAMINATION OF MSCT MASTOID WITH ACUTE MASTOIDITIS CASE IN RSUP DR. KARIADI SEMARANG - Desi Indah Sulistiyo Rini; Suwardi Suwardi (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
Acute mastoiditis refers to suppurative infections of mastoid air cells. The mastoid is an air-filled cavity inside the temporal bone that is connected to the nasopharynx through the eustachian tube and is associated with mastoid water cells through the timpanic antrum (aditus ad antrum). Multislice Computed Tomography (MSCT) is currently the most accurate technique for studying the anatomy and pathology of temporal bones because it offers a very good picture of the ear. Windowing is the process by which the gray scale component of a CT image is manipulated through a CT number. The value of CT number is based on HU value of water which is 0, for bone has HU +1000 value up to +3000 HU, and air has HU -1000 value.This type of research is a qualitative study with an observational approach that aims to determine the MSCT Mastoid examination procedure with cases of mastoiditis in the Radiology Installation of RSUP dr. Kariadi Semarang. This paper was prepared with literature review, observation, unstructured interviews, and documentation in the field.The MSCT Mastoid examination procedure is done by scanning the head with the inner ear protocol. First the topogram is made first and then followed by scanning mastoid. In the case of mastoiditis, it does not require contrast media because the image that will be seen is the temporal bone, especially the mastoid. The image produced from the mastoiditis case shows that the left mastoid air cells are not visible. In this MSCT Mastoid examination windowing used is a bone window with window width 3000 and window level 500. Window width affects the contrast of the image, the higher the window width used, the image will look less contrast. While the window level will affect the level of brigtness (brightness) in the image. The higher the window level value used, the brighter the image.On the MSCT Mastoid examination, the purpose of using the window width 3000 and window level 500 is to see if the bone is forming the mastoid if there is an abnormality. It is expected that with the window width and window level ranges the pathology of mastoiditis can also be seen clearly, as in this case the mastoid air cells in the left area are not visible.